2015
DOI: 10.1016/j.ijcard.2014.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Simple physical performance measures and vascular health in late midlife women: the Study of Women's Health across the nation

Abstract: Background Physical performance measures have been shown to predict mortality and incident cardiovascular disease (CVD) mainly in elderly populations. We evaluated whether physical performance measures are associated with vascular health indices (carotid intima-media thickness (cIMT), adventitial diameter (cAD) and carotid plaque) in a large sample of multi-ethnic, late midlife women. Methods Participants from the Study of Women’s Health Across the Nation free of CVD and who had carotid ultrasound assessed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…All 33 studies were either cross-sectional or randomized controlled trials published within the past 10 years (Table 1). Twenty-three studies [20,26,27,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] included healthy mixed-age adults (age range 18-95) and two studies [53,54] included healthy community-dwelling older adults (age range [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. Six studies sampled participants with hypertension [55][56][57][58][59][60], one study sampled individuals with diabetes as a comparator to healthy aged popula...…”
Section: Study Details and Sample Demographicsmentioning
confidence: 99%
See 3 more Smart Citations
“…All 33 studies were either cross-sectional or randomized controlled trials published within the past 10 years (Table 1). Twenty-three studies [20,26,27,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] included healthy mixed-age adults (age range 18-95) and two studies [53,54] included healthy community-dwelling older adults (age range [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. Six studies sampled participants with hypertension [55][56][57][58][59][60], one study sampled individuals with diabetes as a comparator to healthy aged popula...…”
Section: Study Details and Sample Demographicsmentioning
confidence: 99%
“…Study populations varied from a minimum of 6 [20] to a maximum of 3356 [42] participants. Eight studies included only men [25,27,37,42,49,50,56,61] and four studies included only women [38,52,53,60]. Most studies reported the age range of the participants, except for two studies with one claiming to study "middle-aged" adults [46] and one using adult participants [62].…”
Section: Study Details and Sample Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…6) Khoudary, et al also revealed that poor physical activity performance correlated with vascular structural change. 7) Compared with these similar results, the findings of the current study are most meaningful in the clinical setting because plaque volume reduction is considered to be most influential to clinical outcome.…”
Section: Article P597mentioning
confidence: 54%